2014
DOI: 10.1088/0963-0252/23/2/025012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of collisional quenching of the O 3p3PJstate on the determination of the spatial distribution of the atomic oxygen density in an APPJ operating in ambient air by TALIF

Abstract: . (2014). The effect of collisional quenching of the O 3p 3 P J state on the determination of the spatial distribution of the atomic oxygen density in an APPJ operating in ambient air by TALIF. Plasma Sources Science and Technology, 23(2), 025012-. DOI: 10.1088/0963-0252/23/2/025012 General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 26 publications
5
17
0
Order By: Relevance
“…This increased effect is due to the primary surface modification species being a reactive radical, likely atomic oxygen. It has been reported that this particular MHz APPJ source produces atomic oxygen densities on the order of 10 16 cm −3 for similar conditions used here . This increased thickness loss rate is further evidence that the type of APPJ source used is critical with respect to the surface effect needed as different reactive species have vastly different surface effects.…”
Section: Resultssupporting
confidence: 69%
“…This increased effect is due to the primary surface modification species being a reactive radical, likely atomic oxygen. It has been reported that this particular MHz APPJ source produces atomic oxygen densities on the order of 10 16 cm −3 for similar conditions used here . This increased thickness loss rate is further evidence that the type of APPJ source used is critical with respect to the surface effect needed as different reactive species have vastly different surface effects.…”
Section: Resultssupporting
confidence: 69%
“…The lack an O 3 signature in the TALIF signal is consistent with previous work which has shown [O 3 ] to be low near the plasma jet nozzle, and increase with distance from the nozzle [13,28]. Other work has shown that atomic O content is strongest near the nozzle, and decreases with distance from the nozzle [7,11,13,15] is expected to be somewhat smaller than that measured in plasma jets with 1 -5 % O 2 or air in the gas flow [6,7,22]. The atomic oxygen density produced in the plasma jet increases with RF power, a trend that agrees with previous measurements of [O] in other plasma jet systems [22,31].…”
Section: Resultssupporting
confidence: 89%
“…Finally, Raman scattering was used for evaluating the humid air fraction in the argon effluent. More details about these diagnostics and the measurement conditions and procedures can be found in [10][11][12]15].…”
Section: Methodsmentioning
confidence: 99%
“…One can see that the N 2 (A) density exhibits a much more pronounced time modulation than the NO and O ground state densities (see figure 2 above and figure 3 below). Indeed, van Gessel et al [10] and Zhang et al [15] found that both the NO and O ground state densities are not strongly affected by the power modulation and are constant as a function of time.…”
Section: Time Modulation Of the N 2 (A) Densitymentioning
confidence: 99%
See 1 more Smart Citation